GC-MS ANALYSIS OF PHYTOCHEMICALS IN THE METHANOLIC EXTRACT OF CYCLEA PELTATA. (LAM) HOOK.F & THOMSON - S. JAGADEEP CHANDRA,; N. LAKSHMIDEVI, (International Journal of Pharma and Bio Sciences, 2015)
Cyclea peltata is locally called as “kariballi” belongs to the family Menispermaceae. It is a twining shrub, traditionally used in the treatment of wounds, skin infections and muscular sprains by local folk medicinal practioners. The present study was designed to determine the phytochemical compounds in the methanolic extract of Cyclea peltata by GC-MS analysis. GC-MS chromatogram of the methanolic extract showed six major peaks at retention time of 31.278, 32.742, 35.713, 35.881, 41.244 and 48.947 minutes. The spectrum of the unknown components in the methanol extract was compared with the spectrum of known compounds stored in the NIST library. The mass of the compounds and fragments recorded were matched with NIST database for identification of probable compounds present in the sample and from GC-MS results Twenty five phytochemical compounds were identified.